Living With Semantic Dementia: A Case Study of One Family's Experience. (March 2014) - Kindell, Jacqueline; Sage, Karen; Wilkinson, Ray; Keady, John
Semantic dementia is a variant of frontotemporal dementia and is a recently recognized diagnostic condition. There has been some research quantitatively examining care partner stress and burden in frontotemporal dementia. There are, however, few studies exploring the subjective experiences of family members caring for those with frontotemporal dementia. Increased knowledge of such experiences would allow service providers to tailor intervention, support, and information better. We used a case study design, with thematic narrative analysis applied to interview data, to describe the experiences of a wife and son caring for a husband/father with semantic dementia. Using this approach, we identified four themes: (a) living with routines, (b) policing and protecting, (c) making connections, and (d) being adaptive and flexible. Each of these themes were shared and extended, with the importance of routines in everyday life highlighted. The implications for policy, practice, and research are discussed.